2023
DOI: 10.1186/s12889-023-15283-w
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccination coverage in Egypt: a large-scale national survey – to help achieving vaccination target, March-May, 2022

Abstract: Background Only 57 countries have vaccinated 70% of their population against COVID-19, most of them in high-income countries, whereas almost one billion people in low-income countries remained unvaccinated. In March–May 2022, Egypt's Ministry of Health and Population (MoHP) conducted a nationwide community-based survey to determine COVID-19 vaccine coverage and people's perceptions of vaccination in order to improve COVID-19 vaccination uptake and confidence among Egyptians, as well as to prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
(33 reference statements)
3
3
0
Order By: Relevance
“…Younger individuals, within the age group of 18-39 years, were found to be less likely to vaccinate than their older counterparts, suggesting a decreased perception of COVID-19 susceptibility. This is comparable to a study conducted in Egypt that concluded that the age groups 18-29 and 30-39 years were associated with a low vaccination uptake [30]. A global survey further resonated with our findings, stating older adults were more likely to vaccinate [31].…”
Section: Discussionsupporting
confidence: 89%
“…Younger individuals, within the age group of 18-39 years, were found to be less likely to vaccinate than their older counterparts, suggesting a decreased perception of COVID-19 susceptibility. This is comparable to a study conducted in Egypt that concluded that the age groups 18-29 and 30-39 years were associated with a low vaccination uptake [30]. A global survey further resonated with our findings, stating older adults were more likely to vaccinate [31].…”
Section: Discussionsupporting
confidence: 89%
“…In Egypt, after two years of decline, a resurgence of in uenza and hRSV was reported in children under 16 years of age. Higher infection rates were observed compared to prepandemic period [21].…”
Section: Discussionmentioning
confidence: 86%
“…A wide variety of methods have been used to measure vaccine hesitancy [ 28 ]. Reasons for hesitation include the safety and efficacy of vaccination, considering vaccination unnecessary, and trust issues regarding biomedical research [ 29 ] and the health and surveillance system [ 3 , 30 , 31 ]. One of the most common reasons for vaccine hesitancy is a lack of confidence in the COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%